2017
DOI: 10.3390/en10070837
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis and Neuro-Fuzzy Technique for EOR Screening: Application in Angolan Oilfields

Abstract: In this work, a neuro-fuzzy (NF) simulation study was conducted in order to screen candidate reservoirs for enhanced oil recovery (EOR) projects in Angolan oilfields. First, a knowledge pattern is extracted by combining both the searching potential of fuzzy-logic (FL) and the learning capability of neural network (NN) to make a priori decisions. The extracted knowledge pattern is validated against rock and fluid data trained from successful EOR projects around the world. Then, data from Block K offshore Angola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A soft computing approach can be implemented and investigated to get better performance results. [ 53 ]…”
Section: Suggestions and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A soft computing approach can be implemented and investigated to get better performance results. [ 53 ]…”
Section: Suggestions and Discussionmentioning
confidence: 99%
“…[52] A soft computing approach can be implemented and investigated to get better performance results. [53] The proposed predictive model has improved the performance accuracy. Optimized CNN-based studies can be further examined to obtain higher accuracy.…”
Section: Reservoir Engineeringmentioning
confidence: 91%
See 1 more Smart Citation
“…Table 6 lists the comparison results of the RMSE for the training and testing data for Boston housing data. As listed in Table 6, we finally obtained the best parameters (number of clusters: c = [4,8,9,9,5,9,2], number of rules: 46, weighting exponent: m = 1.5) when the number of linguistic contexts is seven (p = 7). The experimental results clearly showed that the proposed method was superior to the IGM.…”
Section: Automobile Mpg Prediction and Boston Housing Data Setsmentioning
confidence: 99%
“…Figure 12 illustrates the performance of parallel GA across generations. Here, we finally obtained the best parameters (number of clusters: c = [3,9,4,5,9,7,6], weighting exponent: m = 1.9285) when the number of linguistic contexts is seven (p = 7). As shown in Figure 12, we determine the best case of the fitness value across 30 generations when the number of contexts varies from five to eight.…”
Section: Coagulant Dosing Process In a Water Purification Plantmentioning
confidence: 99%